The dead ladies project : exiles, expats, and ex-countries - Crispin, Jessa (University of Chicago Press, 2015)
"When Jessa Crispin was thirty, she burned her settled Chicago life to the ground and took off for Berlin with a pair of suitcases and no plan beyond leaving. Half a decade later, she's still on the road, in search not so much of a home as of understanding, a way of being in the world that demands neither constant struggle nor complete surrender,"--Amazon.com.